1993
DOI: 10.1002/cm.970240107
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases are required for embryonic neural crest cell galvanotaxis

Abstract: Embryonic quail neural crest cells migrate towards the negative pole of an imposed dc electric field as small as 7 mV/mm (0.4 mV per average cell length). The involvement of protein kinases in the mechanism utilized by these cells to detect and respond to such imposed fields was tested through the use of several kinase inhibitors. Evidence for the involvement of protein kinase C (PKC) included: (1) inhibition of the directed motility by 1 microM sphingosine that was reversed by the addition of the phorbol este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…Protein kinase C phosphorylates several cytoskeletal targets, but the precise mechanism by which it induces assembly and extension is unknown. However, inhibitors of protein kinase C do prevent neural crest cells from orienting in an electric field [34]. These inhibitors have no effect on continued directed migration if administered after the cells have already polarized, suggesting that protein kinase C is required for rearrangement of the locomotive machinery, but is not necessary for the continued activity of the machinery.…”
Section: Li/kolegamentioning
confidence: 99%
“…Protein kinase C phosphorylates several cytoskeletal targets, but the precise mechanism by which it induces assembly and extension is unknown. However, inhibitors of protein kinase C do prevent neural crest cells from orienting in an electric field [34]. These inhibitors have no effect on continued directed migration if administered after the cells have already polarized, suggesting that protein kinase C is required for rearrangement of the locomotive machinery, but is not necessary for the continued activity of the machinery.…”
Section: Li/kolegamentioning
confidence: 99%
“…Measurements of [Ca 2+ ]i in mouse embryo fibroblasts, using the Ca 2+ -sensitive photoprotein aequorin, show that application of a dcEF produces a significant overall [Ca 2+ ]i increase (up to mM), which is maintained throughout exposure to the field (Onuma and Hui, 1988). Ca 2+ channel blockers, such as Co 2+ or D600, or removal of extracellular Ca 2+ , can block the dcEF-induced rise in [Ca 2+ ]i (Onuma and Hui, 1988) and, in most cases, this inhibits galvanotaxis without influencing the basic ability of the cell to move (Nuccitelli et al, 1993). dcEF stimulation also more than doubles [Ca 2+ ]i in a rat osteoblast-like cell line (Wang et al, 1998).…”
Section: The Importance Of Ca 2+mentioning
confidence: 99%
“…These include those involving protein kinases such as protein kinase C (Nuccitelli et al, 1993), cGMP-dependent protein kinase and PKA, MLCK (Pullar et al, 2001), CaMKs (Zhuang et al, 1997) and mitogen-activated protein kinase (MAPK) (Zhao et al, 2002a;Zhao et al, 2002b;McBain et al, 2003). Growth factors and their receptors are also implicated, especially epidermal growth factor (EGF), fibroblast growth factor, transforming growth factor (TGF)-β1/α (Zhao et al, 1996;Zhao et al, 2002a), hepatocyte growth factor (McBain et al, 2003) and vascular endothelial growth factor (VEGF) (Zhao et al, 2004).…”
Section: The Influence Of Surface Chargementioning
confidence: 99%
“…Experiments with neural crest cells (Nucitelli et al, 1993) have shown that orientation is modified by inhibitors of protein kinases such as H-7. We have also found that H-7 modifies pollen tube orientation.…”
Section: Asymmetric Activity Of the Apical Cdpk Promotes Reorientationmentioning
confidence: 99%